After Kant, Post-Truth? Ancestrality and Metaphor in Quentin Meillassoux and Graham Harman - Cincunegui, Juan Manuel (Analysis. Journal of Philosophical Research, 2022)
Against Kantian ontology, and idealism in all its forms, Quentin Meillassoux proposes a return to absolute contingency beyond the unknowability imposed by the correlation circle, while Graham Harman, through aesthetics, invites us to recover the dignity of recovering a reality that demands to be treated in an irreducible manner. In the face of the widespread use of new technologies of manipulation and propaganda, which have led to the exacerbation of surveillance and the distortion of truth to the point of its complete inadequacy in relation to reality, turning freedom into a myth, notions of the ancestral and the return to metaphor as the privileged avenues of philosophy, Meillassoux and Harman propose a "recovery of realism" by suggesting an unsubsumable and inappropriate exteriority expressed through mathematics and aesthetics. What political significance such suggestions have is difficult to gauge at this stage. Their theoretical consequences are beyond the will of both authors. Key Words: Speculative realism. Correlationism. Kantism. Idealism. Post-truth